Making the health system work by and for Indigenous women in Guatemala: a community led multisectoral collaboration. (7th December 2018) - Velásquez, Claudia Nieves; del Rosario Garcia Meza, Maria; Ukhova, Daria; Xinico, Silvia; Palma, Susana; Simpson, Sarah
Abstract : Claudia Nieves Velásquez and colleagues report how a community led national alliance of Indigenous women's organisations is working to improve the delivery of healthcare for Indigenous women through collaboration with other community based organisations, government (health and ombudsman), and international partners